Understanding system barriers and facilitators in transnational clinical cancer research: The value of rapid and multimodal ethnographic inquiry - Bright, Kristin (Frontiers in Sociology, 2022)
Introduction In middle and low resource countries worldwide, up to 70% of breast cancer cases are diagnosed as locally advanced (stages IIB-IIIC). Delays in referral from primary to specialty care have been shown to prolong routes to diagnosis and may be associated with higher burdens of advanced disease, but specific clinical and organizational barriers are not well understood. Methods This article reports on the use of rapid ethnographic research (RER) within a largescale clinical trial for locally advanced breast cancer (LABC) in India, Mexico, South Africa, and the US. Our purpose is twofold. First, we demonstrate the value of ethnography as a mode of evaluative listening: appraising the perspectives of diverse patients and clinicians regarding prolonged routes to LABC diagnosis and treatment. Second, we show the value of ethnography as a compass for navigating among discrepant clinical research styles, IRB protocols, and institutional norms and practices. We discuss advantages and limits involved in each use of RER. Results On the one hand, ethnographic interviews carried out before and during the clinical trial enabled more regular communication among investigators and research sites. On the other hand, the logistics of doing the trial placed limits on the extent and duration of inductive, immersive inquiry characteristic of traditional fieldwork. As a partial solution to this problem, we developed a multimodal ethnographic research (MER) approach, an augmentation of video-chat, phone, text, and email carried out with, and built upon the initial connections established in, the in-person fieldwork. This style has its limits; but it did allow us to materially improve the ways in which the medical research proceeded. Discussion In conclusion, we highlight the value of not deferring to a presumed incommensurability of ethnographic fieldwork and clinical trialwork while still being appropriately responsive to moments when the two approaches should be kept apart.